1979
DOI: 10.1111/j.1365-2133.1979.tb00025.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin diseases in Zambia

Abstract: This is the first report on the incidence of skin diseases in Zambians. A diagnostic analysis of 12,610 patients seen over the past year in the Dermatology Clinic at the University Teaching Hospital in Lusaka, Zambia, is presented. The common diseases as well as the peculiarities are discussed. The need to develop research centres in various regions of Africa is emphasized in order to provide better insight into the special dermatological problems seen in the black Africans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 6 publications
1
20
0
Order By: Relevance
“…A major study evaluated 2,720 military recruited for obesity and acne and found this association in only two individuals, aged between 20 and 40 years. No association was found among adolescents aged [15][16][17][18][19] years. This suggests that acne, in a younger population, may be associated with other factors besides obesity and insulin resistance.…”
Section: Hypothesis N 0 1: Obesity and Acne: It Is Not How Much You Ementioning
confidence: 85%
See 3 more Smart Citations
“…A major study evaluated 2,720 military recruited for obesity and acne and found this association in only two individuals, aged between 20 and 40 years. No association was found among adolescents aged [15][16][17][18][19] years. This suggests that acne, in a younger population, may be associated with other factors besides obesity and insulin resistance.…”
Section: Hypothesis N 0 1: Obesity and Acne: It Is Not How Much You Ementioning
confidence: 85%
“…As a starting point, to detect the influence of dietary habits in acne vulgaris, there is a tendency to investigate the food habits of non-Western populations since they do not have acne. [17][18][19][20]32 In their diet, there are no processed foods, dairy, sugars and refined oils. Instead, they eat mainly fresh food, fruit, vegetables, meat, chicken, and grilled seafood.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the prevalence of acne became similar to that in Western societies after their acculturation. Surveys of disease in some rural African villages in Kenya [ 17 ], Zambia [ 18 ], and the Bantu in South Africa [ 19 ] report far less acne than is found in the descendants of these areas who now live in the UK or the USA. More convincing is the study conducted on schoolchildren from Purus Valley, a rural region in Brazil [ 20 ].…”
Section: Ecologic Studiesmentioning
confidence: 96%